A Practical Method of N‐Methylpyrrole Disulfonamides Synthesis: Computational Studies, Carbonic Anhydrase Inhibition and Electrochemical DNA Binding Investigations. Issue 29 (2nd August 2021) - Abas, Mujahid; Nazir, Yasir; Ashraf, Zaman; Iqbal, Zafar; Raza, Hussain; Hassan, Mubashir; Jabeen, Erum; Bais, Abdul
Abstract: Heterocyclic compounds bearing sulfonamide moiety have been reported to possess carbonic anhydrase inhibitory activity. In the present study, a series of novel N ‐methylpyrrole 3 (a –j ) derivatives bearing disulfonamide functional group have been synthesized by following a simple nucleophilic substitution reaction route to explore their carbonic anhydrase inhibitory activity. N ‐methylpyrrole (1 ) was converted into N ‐methylpyrrole disulfonyl chloride (2 ), which upon condensation with various aliphatic and aromatic amines, yielded the final products 3 (a –j ). In silico docking results predicted strong binding of synthesized compounds in an enzymatic pocket of human carbonic anhydrase isozyme II (PDB ID 4Q6D). In vitro carbonic anhydrase inhibitory assays revealed that analogues 3 e (1‐Methyl‐N3, N4‐bis(2‐(pyridin‐2‐yl)ethyl)‐1H‐pyrrole‐3, 4‐disulfonamide) and 3j (N3, N4, 1‐trimethyl‐1H‐pyrrole‐3, 4‐disulfonamide) were most potent with IC50 0.38±0.01 μM and 0.75±0.88 μM respectively in comparison to standard acetazolamide (IC50 0.99±0.04 μM). The enzyme inhibitory kinetics exhibited 3 e a noncompetitive inhibitor with Km and Ki values as 0.34 mM and 18.2 μM respectively. The compounds 3 e and 3 j showed very little cytotoxicity against human keratinocyte (HaCaT) with 80 % cell viability and the anticancer activity performed against MCF‐7 cell line showed that the compounds 3 e and 3 j caused 80 % and 45 % cell death respectively at 125 μM concentrations. Combining the results of DNA binding analysis through the UV‐Vis spectroscopy (hypochromism), cyclic voltammetry (current decrease), and fluorescence spectroscopy (hypochromism in intercalator's peak); mixed binding mode (intercalation + groove binding) was suggested for 3 e and intercalation for 3 j with stronger DNA binding of 3 e than 3 j . Based on our results 3 e and 3 j may be proposed to serve as a lead structure for designing potentially more active CAIs. Abstract : A series of novel sulfonamide‐based N ‐methylpyrrole derivatives 3(a‐j) with various hydrophilic and hydrophobic moieties were synthesized in good yield (68‐75%) to find their role in carbonic anhydrase inhibition depending upon their substitution pattern. The analogue 3e showed excellent CA inhibition with an IC50 0.38 μM better than reference acetazolamide with IC50 0.99 μM in a noncompetitive manner. The in silico and in vitro studies proved 3e and 3j a potent CA inhibitor. Moreover, 3e interacted with DNA through mix binding mode involving intercalation and groove binding.